Slow Violence, Climate Change and Denial in Kingsolver’s Flight Behaviour - Sharma, Kamal (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The paper explores ecological denial, climate change, and life-threatening experiences in both explicit (violent) form and implicit (slow-violent) form in the novel Flight Behaviour by Barbara Kingsolver. As shown in the novel, the sudden appearance of millions of butterflies in Turnbow farming indicates a pleasant and religious theme at surface level, but it signals environmental catastrophe at the underlying level. Ecological denial begins from the home of Dellarobia to the community, disregarding scientific explanations of climate change and the disruption of ecological patterns. This paper argues that much of the denial stems from an anthropocentric perspective echoing climate injustice and human-induced climate change. Dellarobia’s transformation from an ecologically ignorant person to her awakening of ecological self is her assertion of butterflies’ arrival not as ‘God’s sign or Wonder’ but a ‘warning and ecological message.’ The paper backs up its ideas connecting them with United Nations Development Programme (UNDP)’s take on natural and human-induced calamities, Stern’s climate adversities; Ghosh’s the great derangement due to crisis in nature/civilization, and Plumwood’s ecological denial as a result of anthropocentrism. The paper concludes that confronting ecological denial and climate change requires one to rise above personal and social levels, thereby acknowledging ecological justice. The study implies that ignoring seemingly insignificant incident can have tremendous and life-threatening consequences.